Apical hypertrophic cardiomyopathy: Present status. (1st November 2016) - Jan, M. Fuad; Todaro, Maria Chiara; Oreto, Lilia; Tajik, A. Jamil
Abstract: Since the first description of apical hypertrophic cardiomyopathy in Japan 40 years ago, contrasting information from all over the world has emerged regarding the natural history of the disease. This review provides an overview of incidence, phenotypic expressions, clinical features, prognosis, and management of this heterogeneous clinical entity, which may play a more relevant role in the burden of sudden cardiac death than previously thought. Highlights: ApHCM is a complex subset of HCM that is highly heterogeneous in its clinical and pathological profile and predominantly nonobstructive physiologically. Echocardiography provides certainty to the morphology of ApHCM (spectrum and hemodynamic assessment) that characterizes the disease phenotype. CMR reliably detects apical aneurysm and identifies areas of LGE. All patients with ApHCM should undergo risk stratification for sudden death as part of a consummate clinical management protocol involving medications and/or device and surgical options When hypertrophy involves the mid ventricle with MVOCO with or without an apical aneurysm, different morphology, pathophysiology, clinical course, and management gain importance. It is thus incumbent upon the treating physician or cardiologist that he or she strongly considers referral to an HCM clinic with expertise in disease management in the context of contemporary clinical practice.